Assistance for SD Muhammadiyah 20 Sidorejo teachers in using interactive Microsoft Teams - Nurul Kholisatul ‘ulya; Suryanto Nugroho; Septi Aprilia; Sandy Deniawan P.; Adelia Rahmawati (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
The Covid pandemic has entered its second year. During the pandemic SD Muhammadiyah 20 used online learning applications to support learning, namely with the Microsoft team. So far, the Microsoft team has been used for video conferencing, giving assignments, sending learning videos where students are required to learn a lot independently. Do not rule out, in a lesson requires interesting and fun interactions in order to increase interest in learning. As a solution to this problem, training and mentoring are carried out using cool and interactive media, such as delivering material using whiteboards and delivering quizzes using kahoot, each of which has been integrated with the Microsoft team. The method used is that training is then carried out with assistance to teachers as an effort to make it easier for teachers to apply it in learning and then evaluate the activities that have been carried out. From the results of the training, the teachers were enthusiastic in participating in the training and there was feedback and discussion during the training. Next, at the mentoring stage, the majority of teachers have no difficulty in implementing it. Through the questionnaire, it was found that the kahoot application was easy to learn and could be used for interactive learning, while for the ms whiteboard application, not all participants agreed, but it is possible that if the two applications are collaborated, they can be a support for producing interactive learning, especially in the online learning period.